Autotransplantation - Quackery or Science? - Dr Linton Nash (International Dental Journal, 2023)
Introduction: Autotransplantation offers an opportunity for patients who have missing teeth, or teeth with poor prognosis. A transplanted tooth can preserve bone, and restore function and aesthetics in growing patients. Autotransplantation should be considered in cases where there is both dental unit excess and deficiency in the same patient. Case Description: Patients regularly present with ectopic teeth that cannot be retrieved, or with teeth that are missing, avulsed or have a poor prognosis. Three consecutive autotransplantation cases explore the multidisciplinary, decision-making process involving orthodontic, endodontic and 3D surgical planning. Autotransplantation is an effective and predictable alternative for these patients, who would otherwise require delayed and complex prosthodontic solutions. Discussion: Unlike implants, autotransplantation in an option for growing patients and can provide a timely, aesthetic and functional outcome that preserves bone. The advent of 3D surgical planning and printing of tooth analogues and instruments, a novel idea, allows for accurate preparation of the site, minimising extra-oral time and trauma to the donor tooth. These advances along with careful surgical removal help to preserve the periodontal ligament, improving the success of autotransplantation. Conclusion/Clinical Significance: Autotransplantation is a treatment option that dentists should consider for young patients. 3D technology and improved surgical techniques result in success rates for autotransplantation match that of implants, making it a realistic alternative in a growing patient.